2015
DOI: 10.1037/ser0000014
|View full text |Cite|
|
Sign up to set email alerts
|

Utilization of evidence-based psychotherapies in Veterans Affairs posttraumatic stress disorder outpatient clinics.

Abstract: In response to the growing numbers of veterans with posttraumatic stress disorder (PTSD), the Department of Veterans Affairs (VA) has sought to make evidence-based psychotherapies for PTSD available at every VA facility. We conducted a national survey of providers within VA PTSD clinical teams (PCTs) to describe utilization of Prolonged Exposure (PE) and Cognitive Processing Therapy (CPT) and to identify individual and organizational factors associated with treatment uptake and adherence. Participants (N = 128… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
86
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(100 citation statements)
references
References 47 publications
6
86
0
1
Order By: Relevance
“…However, regardless of the therapy a client selects it is critical that therapists follow the therapy protocol. Implementation data from VA and DoD (Borah et al, 2013;Finley et al, 2015;Watts et al, 2014)) is making it clear that when PE and CPT are used by providers, critical components are often left out (e.g., the in-vivo hierarchy in PE). The effectiveness of a given treatment is likely dampened when critical components of the treatment are discarded.…”
Section: The Implementation Of Wet By Austernmentioning
confidence: 99%
See 1 more Smart Citation
“…However, regardless of the therapy a client selects it is critical that therapists follow the therapy protocol. Implementation data from VA and DoD (Borah et al, 2013;Finley et al, 2015;Watts et al, 2014)) is making it clear that when PE and CPT are used by providers, critical components are often left out (e.g., the in-vivo hierarchy in PE). The effectiveness of a given treatment is likely dampened when critical components of the treatment are discarded.…”
Section: The Implementation Of Wet By Austernmentioning
confidence: 99%
“…In addition to the efficacy data, there is emerging evidence that VA and DoD providers are infrequently using these treatments even after receiving training in PE and CPT (Borah et al, 2013;Finley et al, 2015;Watts et al, 2014). Finley and colleagues (2015) found that VA providers used supportive-care treatment approaches for veterans presenting for PTSD treatment substantially more often than PE or CPT, citing high-care demands in combination with limited staff resources as a barrier for not using PE and CPT more often.…”
Section: Special Ptsd Treatment Considerations For Veteran and Activementioning
confidence: 99%
“…Furthermore, as we know, there are a multitude of obstacles in the way of veterans receiving (e.g., Shiner et al, 2013), completing (Hembree et al, 2003), and responding to these first-line treatments (Bradley, Greene, Russ, Dutra, & Westen, 2005;Steenkamp et al, 2015). Providers seeking to offer these treatments may also face obstacles, including working in an understaffed clinic with low emotional support from co-workers (Finley et al, 2015). As Finley and colleagues noted, providers were more likely to offer supportive care (i.e., an alternative, second-line, non-preferred treatment) than PE or CPT, which may potentially be associated with these systemic issues.…”
mentioning
confidence: 99%
“…Major systematic and selective reviews of trials now exist [10][11][12][17][18][19][20][21]. Reviewers present trials classified according to the quality of evidence as recommended by the American Academy of Neurology [22]; they also provide recommendations for clinical application or use of methodologies based on these levels of evidence [10,11].…”
mentioning
confidence: 99%
“…Due to increased vehicular crash-related TBIs, we have implemented preventive measures regarding drunk driving, seat belt use, and helmet use [12]. To date, multiple social-behavioral, targeted therapeutic rehabilitation, and medication intervention trials have been conducted with both civilian and military TBI populations [10][11][12][17][18][19][20][21].…”
mentioning
confidence: 99%